Accurate, sensitive determination of omega-6 and omega-3 polyunsaturated fatty acids in human plasma, urine samples - Er, Elif Ozturk; Sahin, Ayse; Bakirdere, Sezgin (WILEY, 2020)
Quantitative determination of omega-6 and omega-3 polyunsaturated fatty acids in human plasma and urine with high accuracy and precision provides significant information to monitor the underlying etiology of several diseases. In this regard, liquid chromatography-mass spectrometry is a good choice owing to its great selectivity and sensitivity. Additionally, the hybrid quadrupole-time of flight-mass spectrometer systems provides easy identification of target compounds with superior mass measurements. In this study, an analytical method has been developed for simple, accurate and simultaneous determination of linoleic acid, arachidonic acid, docosahexaenoic acid and eicosapentaenoic acid in a short chromatographic analysis period. The developed method is suitable for the quantitative detection of these four compounds with detection limits ranging between 1.1-3.0 ng ml(-1)and its applicability was assessed in human urine and plasma samples. As a result, acceptable accuracy (between 83 and 111%) and good precision (<6%) were obtained for target compounds using matrix matching calibration strategy.
Keywords: human plasma; human urine; liquid chromatography-mass spectrometry; matrix-matching calibration strategy; polyunsaturated fatty acids; GAS-CHROMATOGRAPHY; SPECTROMETRY ANALYSIS; MASS SPECTROMETRY; FISH-OIL; OMEGA-3-FATTY-ACIDS; VALIDATION; HPLC; Biochemistry & Molecular Biology; Chemistry; Pharmacology & Pharmacy